2017
DOI: 10.1007/s00421-017-3742-6
|View full text |Cite
|
Sign up to set email alerts
|

A random-perturbation therapy in chronic non-specific low-back pain patients: a randomised controlled trial

Abstract: The purpose of the study was to assess the effectiveness of a specific rehabilitation therapy for chronic non-specific low-back pain patients, based on a random/irregular functional perturbation training induced by force disturbances to the spine. Forty patients (20 controls and 20 in the perturbation-based group) finished the whole experimental design. A random-perturbation exercise, which included variable and unpredictable disturbances, was implemented in the therapy of the perturbation-based group (13 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 45 publications
0
40
1
Order By: Relevance
“…Similar results (i.e., no LBP effects on local dynamic stability of trunk kinematics) were also reported by Graham et al (2014) and Asgari et al (2015) . A recent study ( Arampatzis et al, 2017 ) also found unchanged local dynamic stability of the trunk motion despite a significant reduction in LBP after an exercise therapy. To our knowledge, the only study that reported increased instability of trunk kinematics in the presence of LBP ( Ross et al, 2015 ) used a heat-capsaicin model to introduce the LBP.…”
Section: Discussionmentioning
confidence: 85%
“…Similar results (i.e., no LBP effects on local dynamic stability of trunk kinematics) were also reported by Graham et al (2014) and Asgari et al (2015) . A recent study ( Arampatzis et al, 2017 ) also found unchanged local dynamic stability of the trunk motion despite a significant reduction in LBP after an exercise therapy. To our knowledge, the only study that reported increased instability of trunk kinematics in the presence of LBP ( Ross et al, 2015 ) used a heat-capsaicin model to introduce the LBP.…”
Section: Discussionmentioning
confidence: 85%
“…All four exercises will be performed with three sets of 10 repetitions each, with a minimum of 30 s rest in between sets (unpublished material, RCT (MiSpEx), German Clinical Trials Register No. DRKS00004977, [ 13 , 14 ]). In between exercises, a 2-min break (self-controlled) is allowed.…”
Section: Methodsmentioning
confidence: 99%
“…4 ). Subjective rating of load-induced back pain is assessed directly before and after the trunk-loading protocol (Visual Analog Scale VAS: 0.0–10.0 cm) to control for possible pain effects [ 13 , 14 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensorimotor training (SMT) consisted of two parts: a three-week supervised center-based training program, followed by a nine-week individual homebased training (see also [31][32][33]). In both phases of the program, participants trained three times a week.…”
Section: Sensorimotor Trainingmentioning
confidence: 99%